The Correlation Between Punctuation and Narrative Writing on the Communication Students of BSI University - Wibowo, Ary Iswanto; Rahayuningsih, Retno; Khairunas, Sayyid (English Education Department, Faculty of Teacher Training and Education, Islamic University of Jember, 2025)
This research is made as a result of issue of error punctuation usage and narrative writing. It is scrutinized by using correlation research method. The data was taken from population of second year academic communication’s students of BSI through the sampling unit consists of 37 students. The result of the research was elaborated into three categories. They are low, middle, and high. Based on variable of punctuation usage, the low grade defined 21,62% or 8 students, the middle grade defined 65,75% or 21 students, and the high grade defined 21,62% or 8 students. Furthermore, based on narrative writing, the low grade set 24,32% or 9 students, the middle grade set 51,35%, and the high grade set 24,32% or 9 students. Then, the researchers resulted “r count” = 0,5956 and “r table” = 0,334 or 0,430. The calculation showed that “r count” was bigger than “r table”. It means that there was a significant correlation between punctuation usage and narrative writing among the second-year communication sciences students. Through the finding and looking at middle category grade, it can be summed up that there was significant study between punctuation usage and narrative writing.